Research Activities on the Forest Line in Northern Finland - Kallio, Paavo; Hurme, Heli; Eurola, Seppo; Norokorpi, Yrjö; Sepponen, Pentti (ARCTIC, 1986)
Forest line research is one of the main areas of study open to the northern research stations, especially numerous in Fennoscandia. High latitude environmental conditions make considerable demands on the adaptability of plants growing in the subarctic. Besides low temperatures, low light intensity and low energy yield are a challenge to autotrophs: the light rhythm is quite different from that farther south. Detailed mapping of the forest line is now undertaken every 10 years in northern Finland to study the climatic changes causing shifts in the limit. All 12 monitoring areas are situated north of the Arctic Circle. Similar monitoring may be started in other Fennoscandian countries in the near future and might prove useful for studying the effect of the general pollution of the forests. One of Finland's many northern research stations is at Kevo and belongs to the University of Turku. It is the site of the Circumpolar Forest Line Arboretum, where material is collected from all the circumpolar areas. There are three gardens altogether: one close to the station, and the others at a distance of some 10 km. They are managed jointly by the Kevo Station, the National Board of Forestry and the Forest Research Institute. Cooperation in northern research has a long history in Fennoscandia; for example, the project started during the IBP period for studying the northern birch zone continued the work begun by Wahlenberg at the start of the 19th century. The project deals mainly with the variation of the birch and other components of this northern ecosystem. Attention is also paid to the stimulating question of the co-evolution of the different organisms.Key words: arboretum, circumpolar, monitoring, mountain birch, treeline, tree provenances Mots clés: arboretum, circonpolaire, surveillance, bouleau des montagnes, limite forestière, provenance des arbres